Iron trial results pave the way for improved haemodialysis treatment. (2nd March 2019) - Thompson, Maria
Abstract : An update of the Kidney Research UK-facilitated clinical trial results, designed to determine the optimum dose of intravenous iron for a kidney patient on haemodialysis, has been published in the New England Journal of Medicine . In this article, Maria Thompson describes the findings